CERÁMICAS TARDÍAS DE PRODUCCIÓN EGIPCIA EN CARTHAGO NOVA - Amante Sánchez, Manuel; Pérez Bonet, Mª Ángeles (Antigüedad y Cristianismo, 1995)
In this work a study is made of the unedited collection of Egyptian made vases found during an excavation in the site located at C/ Palas 8, Cartagena, Murcia, where a Late Roma dumpingplace was found. It is dated to the last years of the fifth century and the first years of the sixth century a.c.